Single-Arm, Multicenter Phase I/II Clinical Trial for the Treatment of Envenomings by Massive Africanized Honey Bee Stings Using the Unique Apilic Antivenom - Barbosa, Alexandre Naime; Ferreira, Rui Seabra; de Carvalho, Francilene Capel Tavares; Schuelter-Trevisol, Fabiana; Mendes, Mônica Bannwart; Mendonça, Bruna Cavecci; Batista, José Nixon; Trevisol, Daisson José; Boyer, Leslie; Chippaux, Jean-Philippe; Medolago, Natália Bronzatto; Cassaro, Claudia Vilalva; et al. (Frontiers in Immunology, 2021)
We evaluated the safety, optimal dose, and preliminary effectiveness of a new-approach Africanized honeybee (Apis mellifera) Antivenom (AAV) in a phase I/II, multicenter, non-randomized, single-arm clinical trial involving 20 participants with multiple stings. Participants received 2 to 10 vials of AAV depending on the number of stings they suffered, or a predefined adjuvant, symptomatic, and complementary treatment. The primary safety endpoint was the occurrence of early adverse reactions within the first 24 h of treatment. Preliminary efficacy based on clinical evolution, including laboratory findings, was assessed at baseline and at various time points over the four following weeks. ELISA assays and mass spectrometry were used to estimate venom pharmacokinetics before, during, and after treatment. Twenty adult participants, i.e., 13 (65%) men and 7 (35%) women, with a median age of 44 years and a mean body surface area of 1.92 m2 (median = 1.93 m2) were recruited. The number of stings ranged from 7 to > 2,000, with a median of 52.5. Symptoms of envenoming were classified as mild, moderate, or severe in 80% (16), 15% (3), and 5% (1) of patients, respectively; patients with mild, moderate, or severe envenoming received 2, 6, and 10 vials of AAV as per the protocol. None of the patients had late reactions (serum sickness) within 30 d of treatment. There was no discontinuation of the protocol due to adverse events, and there were no serious adverse events. One patient had a moderate adverse event, transient itchy skin, and erythroderma. All participants completed the intravenous antivenom infusion within 2 h, and there was no loss to follow-up after discharge. ELISA assays showed venom (melittin and PLA2) concentrations varying between 0.25 and 1.479 ng/mL prior to treatment. Venom levels decreased in all patients during the hospitalization period. Surprisingly, in nine cases (45%), despite clinical recovery and the absence of symptoms, venom levels increased again during outpatient care 10 d after discharge. Mass spectrometry showed melittin in eight participants, 30 d after treatment. Considering the promising safety results for this investigational product in the treatment of massive Africanized honeybee attack, and its efficacy, reflected in the clinical improvements and corresponding immediate decrease in blood venom levels, the AAV has shown to be safe for human use. Clinical Trial Registration: UTN: U1111-1160-7011, identifier [RBR-3fthf8].